Retrospective Evaluation of Factors That Influence the Implementation of CATCH in Southern Illinois Schools. Issue 5 (September 2014) - Bice, Matthew R.; Brown, Stephen L.; Parry, Thomas
Background . Coordinated Approach to Child Health (CATCH) is a school health program implemented in southern Illinois that focuses on physical activity and nutrition and consists of a classroom curriculum, physical education framework, and cafeteria guidelines. Though many schools agreed to implement CATCH, some schools implemented it better than others. This study examined implementation practices of classroom and physical education teachers and cafeteria supervisors. Method . We surveyed 284 school employees at 36 elementary schools located in southern Illinois. Attention focused on organizational readiness, commitment to change, school leadership, implementation barriers, and innovation perceptions concerning degree of implementation of CATCH. Results . Organizational readiness and implementation barriers were significant predictors of degree of implementation for school employees. Additionally, organizational readiness was reported a significant predictor of classroom teacher degree of implementation whereas leadership was a significant predictor of degree of implementation by physical education teachers. Conclusion . Data from this study can be used to enhance implementation of CATCH as well as other school health programs. This study provides educators evidence of why school employees have different implementation practices, evidence of what constructs influence degree of implementation most, and some explanation of school employee degree of implementation.